2009
DOI: 10.1016/j.otohns.2008.10.027
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effect of ginkgo biloba extract in myringosclerosis: Study in rats

Abstract: Formation of experimental myringosclerosis was reduced or inhibited and tympanic membranes were thinner after systemic Ginkgo biloba extract administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…In some studies, several free radical scavengers were used to prevent the development of MS in TM [7][8][9][10][11][18][19][20][21][22][23]. Mattson et al reported that copper zinc superoxide dismutase and catalase and deferrioxamine prevented the development of MS [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies, several free radical scavengers were used to prevent the development of MS in TM [7][8][9][10][11][18][19][20][21][22][23]. Mattson et al reported that copper zinc superoxide dismutase and catalase and deferrioxamine prevented the development of MS [19].…”
Section: Discussionmentioning
confidence: 99%
“…In a study from Kazikdas et al, have reported that the occurrence of myringosclerosis following experimental myringotomy could be hindered by systemic melatonin treatment [10]. Emir et al Investigated the effect of systemic Ginkgo biloba extract administration and reported that formation of experimental myringosclerosis was reduced or inhibited as well as tympanic membranes were found to be thinner [11]. Song et al used caffeic acid phenyl ester (CAPE), a biologically active ingredient in propolis, and Dogan et al used N-nitro L-arginine metyl ester (L-NAME), a competitive inhibitor of nitric oxide synthase (NOS), and they concluded that treatment with either CAPE or L-NAME provided reduction in inflammation as well as fibrosis in lamina propria of TM and prevented the formation of MS [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathological examination was performed on the 15 th postoperative day, in accordance with previously performed and published studies [8][9][10][11] .…”
Section: Methodsmentioning
confidence: 99%
“…MS occurs as a result of the healing process with fibrosis and calcification seen after irreversible tissue damage. Consequently, it was aimed to inhibit the production and harmful effects of oxygen derived free radicals to prevent MS. Several free radical scavengers, antioxidants and antiinflammatory drugs have been used for this purpose [1,4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%